Research of Trend Gastro Diplomacy in Indonesia - Humairah Muljabar (Journal of Islamic World and Politics, 2024)
Gastrodiplomacy, as a form of cultural diplomacy, can play a bigger and more efficient role in increasing awareness of the nation's image and building national identity through food. This article will examine the effectiveness of gastro diplomacy as part of cultural diplomacy in increasing awareness of the nation's image and forming national identity through food, as well as the extent to which research trends and patterns regarding gastro diplomacy can be mapped through bibliometric analysis to identify contributions, collaborations and research developments in the field. This research aims to determine and analyze trends in gastro diplomacy research topics in Indonesia for 2017-2022 using bibliometric studies. The method used in this research was quantitative research methods. The population was all articles with gastro diplomacy topics in Indonesia from 2017-2022. The data search process in this research used Publish or Perish in the Google database. The Vosviewer application was used to visualize the bibliometric analysis. The results showed that the highest growth in research on gastrodiplomacy occurred in 2021, reaching 31 publications (32.63%). Meanwhile, the lowest number of publications occurred in 2017, with 3 (3.16%). Bibliometric analysis based on researchers or authors was centered on "Hidayat," who was active in conducting research around gastro diplomacy topics, with four publications from 2017 - 2022. Developments of gastro diplomacy based on co-occurrence (keywords) from 104 articles indexed by Google Scholar can be grouped into 7 clusters such as country, South Korean gastro diplomacy, Korean cuisine, Kitcehem, gastro diplomacy case studies, Thailand, and so on.